2005
DOI: 10.1007/s00122-005-1988-6
|View full text |Cite
|
Sign up to set email alerts
|

Allelic reduction and genetic shift in the Canadian hard red spring wheat germplasm released from 1845 to 2004

Abstract: Analysis of genetic diversity changes in existing gene pools of cultivated crops is important for understanding the impact of plant breeding on crop genetic diversity and developing effective indicators for genetic diversity of cultivated plants. The objective of this study was to assess genetic diversity changes in 75 Canadian hard red wheat (Triticum aestivum L.) cultivars released from 1845 to 2004 using 31 simple sequence repeats (SSRs) markers. A total of 267 SSR alleles were detected, and their allelic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
55
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 34 publications
6
55
2
Order By: Relevance
“…About 15 individual samples for each population of emmer wheat or wild barley in either sampling period were randomly selected. Young leaf tissues were collected for DNA extraction and quantification as described previously (30). SSR analysis (18) was performed using 32 wheat and 29 barley SSR primer pairs (SI Appendix, Table S3), as described previously (30)(31)(32).…”
Section: Methodsmentioning
confidence: 99%
“…About 15 individual samples for each population of emmer wheat or wild barley in either sampling period were randomly selected. Young leaf tissues were collected for DNA extraction and quantification as described previously (30). SSR analysis (18) was performed using 32 wheat and 29 barley SSR primer pairs (SI Appendix, Table S3), as described previously (30)(31)(32).…”
Section: Methodsmentioning
confidence: 99%
“…The coefficient of parentage, or degree of relatedness, among a sample of CWRS cultivars was higher from the 1970s to the 1990s (0.58) than from the 1940s to the 1970s (0.31) or prior to 1941 (0.18) (van Beuningen and Busch 1997). There was also a general increase in the degree of genetic similarity between CWRS cultivars from the period from 1910 to 2004 for microsatellite markers derived from either genomic DNA sequence (Fu et al 2005) or expressed sequence tags (Fu et al 2006).…”
Section: Canada Western Red Spring Wheat (Cwrs)mentioning
confidence: 97%
“…The loss of genetic diversity due to modern breeding practices has been reported in several studies (Fu et al, 2005). Several authors have shown that the narrowness of crop genetic diversity could lead to increased susceptibility to diseases and pests, as well as the inability of plants to respond to different environmental constraints (Gorji and Zolnoori, 2011).…”
Section: Introductionmentioning
confidence: 99%